Originary Sin - Gans, Eric Lawrence (2020)
For Matthew Taylor The holiday of Simchat (Simchas in the old days) Torah, which fell this year on October 11, celebrates God’s gift of the Torah to the Hebrews. It involves scrolling back to the beginning of the Pentateuch to recommence the yearly reading of the five books. As everyone knows, the Torah begins with...